Coronary Artery Rupture Caused by Stent Infection: A Rare Complication. Issue 14 (7th April 2015) - Roubelakis, Apostolos; Rawlins, John; Baliulis, Giedrius; Olsen, Sally; Corbett, Simon; Kaarne, Markku; Curzen, Nick
Abstract : Supplemental Digital Content is available in the text.